ANALISIS KEBUTUHAN PENGEMBANGAN INSTRUMEN PENILAIAN TWO TIER MULTIPLE CHOICE MENJELAJAHI SISTEM SURYA BAGI PESERTA DIDIK SEKOLAH DASAR BERBASIS BAMBOOZLE - Br Kembaren, Desy Putri Egina; Tri Suminar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Development of instruments is an important step to ensure that the assessment process can be conducted objectively, fairly, and in accordance with educational goals. A good instrument not only measures students' learning outcomes but also assists educators in designing instruction, improving the quality of education, and shaping students' character and abilities in line with current demands. In the context of IPAS (Science and Environmental Studies) learning, especially on the topic of exploring the solar system, an appropriate assessment instrument is needed that can develop students' critical thinking skills. The purpose of this study is to analyze the need for developing a two-tier multiple choice assessment instrument on exploring the solar system for students, based on the Bamboozle platform. This research is qualitative, with data collection techniques including interviews, observations, and questionnaires distributed to students to identify the need for developing a two-tier multiple choice instrument based on Bamboozle. The subjects of this study consisted of sixth-grade elementary school teachers and students in Toba Regency. Data obtained from interviews, observations, and questionnaires were analyzed descriptively. The results show that educators do not yet have a two-tier multiple choice assessment instrument on exploring the solar system for elementary students based on Bamboozle. Educators recognize the importance of developing a two-tier multiple choice assessment instrument but are still constrained by a lack of ability to develop it. Most students also acknowledge that this two-tier multiple choice assessment instrument is important to develop. Therefore, it can be concluded that the development of a two-tier multiple choice assessment instrument on exploring the solar system for elementary students based on Bamboozle is important and needed.